PCI in patients with ostium coronary artery lesions: three-year follow-up. (25th November 2020) - Maximkin, D; Shugushev, Z; Chepurnoy, A; Safonova, O; Mambetov, A; Gitelzon, E; Faibushevich, A
Abstract: Aims: To increase the effectiveness of percutaneous coronary interventions (PCI) in patients with ostium coronary artery lesions. Methods: 170 patients were included in the study. Inclusion criteria: ostium atheroslerotic lesions of left arterial descending (LAD) or left circumflex (LCx) >70% according to angiography and intravascular ultrasound (IVUS); myocardial ischemia according stress test and FFR measurement. All patients were randomized into 2 groups. In I group (n=85) according to IVUS, atherosclerotic plaque spread from the ostium of LAD and/or LCx to the left main coronary artery (LMCA), and in group II (n=85) - the plaque did not spread into the LMCA. In Group I all patients were initially treated with "Provisional T" stenting of the LMCA, and in Group II – precision stenting of the ostium LAD or LCx. Long-term results were evaluated on 24 and 48 months. Primary endpoints: frequency of MACE (death, MI, revascularizations). Results: During hospitalization of complications associated with PCI was not, survival was 100% in all groups. The conversion to complete bifurcation stenting were in 5 patients from Group I and conversion to provisional stenting were in 3 patients from Group II. The long-term results after 24 months was observe in 70 patients from Group I and 72 patients, from Group II. Nonfatal myocardial infarction (MI) was observed in 2 (2.7%) of patients from group II and not in Group I. The incidence of hemodynamic significant stent restenosis and was observed in 4 patients (5.7%) in Group I, and in 7 patients (9.8%) in Group II (p<0.05). The target lesion revascularization (TLR) was performed in 4 patients (5.7%) in Group I, and in 9 patients (12.5%) in Group II (p<0.05). The total frequency of MACE in groups I and II was 4 (5.7%) and 9 (12.5%), respectively (p<0.05). The survival was 100% in both groups. The long-term results after 48 months was observe in 58 patients from Group I and 54 patients, from Group II. All type of death registration in 1 patient from Group I and 2 patients from Group II. Nonfatal myocardial infarction (MI) was observed in 1 patient (1.7%) and 2 patients from Group II (3.7%) (p>0.05). The incidence of hemodynamic significant stent restenosis was observed in 3 patients (5.7%) in Group I, and in 5 patients (9.3%) in Group II (p<0.05). The target lesion revascularization (TLR) was performed in 4 patient (6.9%) in Group I, and in 7 patient (13%) in Group II (p<0.05). The total frequency of MACE in groups I and II was 5 (8.6%) and 10 (18.5%), respectively (p<0.05). The freedom from cardiac events (Kaplan-Maier analysis) was significant difference (92.5 in Group I and 84.5 in Group II (p<0.05). Conclusions: IVUS analysis of ostium stenosis of coronary arteries can help in choosing the optimal stenting technique, as well as reliably improve long-term PCI results. Patients after precision stenting of the ostium have worse long-term results, compared with patients after provisional T-stenting. Funding Acknowledgement: Type of funding source: None